2018
DOI: 10.3390/rs10050778
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Texture Features to Classify Coastal Wetland Vegetation from High Spatial Resolution Imagery Using Completed Local Binary Patterns (CLBP)

Abstract: Abstract:Coastal wetland vegetation is a vital component that plays an important role in environmental protection and the maintenance of the ecological balance. As such, the efficient classification of coastal wetland vegetation types is key to the preservation of wetlands. Based on its detailed spatial information, high spatial resolution imagery constitutes an important tool for extracting suitable texture features for improving the accuracy of classification. In this paper, a texture feature, Completed Loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Huang et al [31] found that pixel-based morphological profiles significantly outperformed object-based GLCM textures for forest mapping and species classification. Wang et al [32] tested the Completed Local Binary Patterns (CLBP) textures originally designed for face recognition and found that the textures were suitable for classifying wetland vegetation using SVM. With recent advances in machine learning, deep learning models (e.g., CNNs) have achieved great success in computer vision and pattern recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [31] found that pixel-based morphological profiles significantly outperformed object-based GLCM textures for forest mapping and species classification. Wang et al [32] tested the Completed Local Binary Patterns (CLBP) textures originally designed for face recognition and found that the textures were suitable for classifying wetland vegetation using SVM. With recent advances in machine learning, deep learning models (e.g., CNNs) have achieved great success in computer vision and pattern recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Jia adopted an object-oriented classification method on Landsat data to map the spatial distribution of mangrove areas in coastal wetlands of China and obtained accurate results [44]. Wang explored the potentials of completed local binary patterns (CLBP) in extracting texture feature and applied it to classify vegetation in Yancheng coastal wetlands of China [45]. Unfortunately, determining proper spatial-object features is time consuming and the performance of object-based classifier might diverge greatly across different features selected.…”
Section: Introductionmentioning
confidence: 99%
“…One of the areas of application of GLCM textural metrics is land cover classification. Over the years, many studies have used these GLCM textural metrics to either create or improve models that discriminate land cover types [37][38][39][40][41][42]. Treitz et al [43] utilized GLCM textural measures derived from C-band SAR data to improve discrimination of different agricultural crops from a Kappa value of 39% to 78%.…”
Section: Introductionmentioning
confidence: 99%